Overview of Public Knowledge about the Benefits of Prayer for Musculoskeletal Health - Setianto, Gigih; Setyawan, Muhammad Ghilang Maulud; Risdiani, Risdiani (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to describe the level of knowledge of the community, especially Aisyiyah Doro members, about the benefits of prayer for musculoskeletal health. Prayer, which involves a variety of body movements such as standing, crouching, prostrating, and sitting, is recognized to have significant benefits for physical health, including muscle flexibility, joint flexibility, and blood circulation. This study uses a quantitative descriptive method with 30 respondents who are selected through the purposive sampling technique. The instrument used was in the form of a questionnaire with questions validated by religious and health experts, and tested for reliability using Alpha Cronbach. The data was analyzed descriptively using frequency and percentage distributions. The results showed that the majority of respondents had a good awareness of the benefits of prayer for musculoskeletal health, with 86.7% understanding the benefits of movements such as bowing and prostrating on muscles and joints. As many as 70% of respondents reported feeling immediate physical benefits from prayer, such as a decrease in muscle and joint pain, as well as an increase in body flexibility. In addition, 80% of respondents stated that they felt healthier after performing prayers regularly